DNA damage in BALB/c mice infected with Lacazia loboi and its relation to nutritional status - Assencio Almeida Barbosa, Adriana Sierra; Cardoso de Oliveira, Larissa Ragozo [UNESP]; Tavares, Francilene Capel [UNESP]; Goncalves de Lima, Carlos Roberto [UNESP]; Diorio, Suzana Madeira; Calvi, Sueli Aparecida [UNESP]; Vilani-Moreno, Fatima Regina; Marques Pereira, Paulo Camara [UNESP] (Biomed Central Ltd, 2015)
Background: Jorge Lobo's disease, also known as lacaziosis, is a cutaneous-subcutaneous mycosis with chronic evolution. It is caused by the fungus Lacazia loboi. Herein we report a study that relates the genotoxicity caused by L. loboi in isogenic mice with nutritional status, through a normal or restricted diet.Methods: DNA damage was assessed in the peripheral blood by the comet assay (tail intensity).Results: The results for leukocytes showed increases in the mean tail intensity in mice under dietary restriction, in infected mice under dietary restriction and in infected mice ingesting a normal diet.Conclusion: These results indicate that dietary restriction and L. loboi infection may increase DNA damage levels in mice, as detected by the comet assay.
Keywords: Jorge Lobo'disease; Lacazia loboi; Malnutrition; Mice; Genotoxicity; Comet assay